Pajak dan Kesadaran Masyarakat menjadi Pilar Utama Pembangunan Nasional dalam Upaya Meningkatkan Penerimaan Negara - Okia Agati Br Ginting; Grace Eklysya Br Sitepu; Lorita Tarigan; Shinta Klara Br Tarigan; Rohani Br Sihotang (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
Taxes are a primary source of state revenue and play a crucial role in supporting national development. However, increasing tax revenue still faces several challenges, particularly the lack of public awareness in fulfilling tax obligations. This study aims to examine the role of public awareness in improving taxpayer compliance and its impact on state revenue. The approach used in this research is qualitative, reviewing literature from various previous studies. Research findings indicate that tax awareness, understanding, and knowledge have a positive impact on taxpayer compliance. Other economic factors such as inflation, population, and economic growth also play a role in influencing tax revenue. However, external factors such as socialization and tax sanctions show inconsistent results. Consequently, increasing public awareness through tax education is a key strategy for sustainably improving the country's performance. In addition, transparent tax management and effective government communication are important factors in strengthening public trust and encouraging voluntary taxpayer compliance. Therefore, collaboration between the government and society is needed to create a sustainable and effective taxation system that supports national economic growth.